PENGARUH PENGGUNAAN INSTAGRAM STORIES TERHADAP PENGUNGKAPAN DIRI SISWA SMA NEGERI 8 MAKASSAR (STUDI DESKRIPTIF KUANTITATIF) - Ummul Wafiah; Mudzhira Nur Amrullah; Harmin Hatta (Fakultas Dakwah dan Komunikasi, 2020)
The purpose of this study was to determine the level of use of Instagram stories among students of SMA Negeri 8 Makassar. This is to determine the level of self-disclosure of students of SMA Negeri 8 Makassar. To find out the effect of using Instagram stories on self-disclosure of SMA Negeri 8 Makassar students. The results showed that the majority of students at SMA Negeri 8 Makassar had a moderate level of use of Instagram Stories with a percentage of 61% (45 students, meaning that students with moderate use of Instagram Stories are students who use social media just to see media content and rarely upload. Good status in the form of writing, uploading photos, or videos. Meanwhile, for the level of self-disclosure of SMA Negeri 8 Makassar it was also found that the majority of SMA Negeri 8 Makassar students had moderate self-disclosure with a percentage of 45% (33 students), meaning that the level of disclosure moderate self, this is because students do not really express themselves.